(untitled) (Praxis Educativa, 2015)
The present work attempts to articulate some theoretical issues that will allow us to think of the elements of a critical mode of tension produced between the social place rhetorically assigned to work and the teachers work as well as the world of ideological representations that are real and in an effective form and objectively operates these terms. We believe that despite all transitions of a decade in this new millennium, there are issues related with fundamental issues of gender, class and ethnicity that demands to be addressed and problematized in educational fields. For example, we will take the case of the tragedy of seven teachers who due to their hard work were killed on the Santafesine roads in Argentina. We will highlight the tip of the iceberg that is our point of departure for our reflection and debate on the conditions of teachers and their role in this new conjuncture in our recent history.